Investigation of the growth performance, blood status, gut microbiome and metabolites of rabbit fed with low-nicotine tobacco - Jing, Changliang; Wang, Jiahao; Xie, Yi; Zhang, Jianhui; Guo, Yixuan; Tian, Tian; Tang, Jing; Ju, Fuzhu; Wang, Chunkai; Liu, Yanhua; Zhang, Zhongfeng; Yang, Xingyou; et al. (Frontiers in Microbiology, 2022)
Tobacco contains a large amount of bioactive ingredients which can be used as source of feed. The objective of this study was to evaluate the effects of dietary addition of low-nicotine tobacco (LNT) on the growth performance, blood status, cecum microbiota and metabolite composition of meat rabbits. A total of 80 Kangda meat rabbits of similar weight were assigned randomly as four groups, and three of them were supplemented with 5%, 10%, and 20% LNT, respectively, with the other one fed with basal diet as control group. Each experiment group with 20 rabbits was raised in a single cage. The experiments lasted for 40 days with a predictive period of 7 days. The results revealed that LNT supplementation had no significant effect on the growth performance, but increased the half carcass weight compared with control group. Dietary supplemention of LNT decreased the triglycerides and cholesterol content in rabbit serum, and significantly increased the plasma concentration of lymphocytes (LYM), monocytes, eosinophils, hemoglobin HGB and red blood cells. In addition, LNT supplementation significantly changed the microbial diversity and richness, and metagenomic analysis showed that LNT supplementation significantly increased Eubacterium_siraeum_group, Alistipes, Monoglobus and Marvinbryantia at genus level. Moreover, LC–MS data analysis identified a total of 308 metabolites that markedly differed after LNT addition, with 190 significantly upregulated metabolites and 118 significantly downregulated metabolites. Furthermore, the correlation analysis showed that there was a significant correlation between the microbial difference and the rabbit growth performance. Overall, these findings provide theoretical basis and data support for the application of LNT in rabbits.